The association between frailty status and cognitive function in patients with cardiovascular diseases: a nationwide cohort study - Wanchunxue Jiang; Meng Wei; Qianhui Wang; Pengcheng Fan; Zukela Tuerhong; Yanmei Lu; Baopeng Tang; Xianhui Zhou (Scientific Reports)
Abstract In individuals with cardiovascular disease, the commonly observed comorbid conditions are frailty and cognitive impairment. However, currently, the impact of cognitive function on frailty and the dynamic interplay between both in patients with cardiovascular disease are ambiguous. This cohort study explored the association between frailty and cognitive function in Chinese adults with cardiovascular conditions, specifically focusing on those who were middle-aged or older. This study aims to elucidate the temporal interactions and potential causal relationships between these two variables by incorporating a cross-lagged panel model analysis. Cognitive function was observed to significantly predict cognitive function at the subsequent time point using autoregressive analysis within the cross-lagged model (β = 1.105, P < 0.001). Significant temporal variations were identified in the impact of early stage of frailty status on cognitive function in the bidirectional interaction assessment (β = 0.293, P = 0.006). However, a shift was noted in later stages, with a significantly negative effect of the frailty status on the cognitive function from the third to the fourth wave (β = −1.102, P < 0.001). Both frailty status and cognitive function exhibit a certain degree of temporal stability and a significant bidirectional association.